Future Technology and the Evolution of Student Spirituality in Sufi Contexts - Boy Arief Rochman (Khazanah Pendidikan Islam, 2025)
The research aims to explore how future technology influences the evolution of student spirituality within the Sufi context, particularly in the practice of the Naqshbandi Tariqah. The findings indicate that future technology has significant potential to enhance accessibility to spiritual or tasawuf resources, such as classical texts, lectures, and educational materials. Additionally, virtual communities play a crucial role in supporting interaction and sharing spiritual experiences among students. Technology also enriches spiritual experiences through meditation apps, lecture videos, and online discussion forums. However, the study also identifies several risks associated with the use of technology, such as distractions from irrelevant content, the selection of inappropriate content, and limitations in facilitating direct meetings with spiritual communities and mentors. Therefore, it is important to develop well-curated digital platforms, digital education programs, and safe and supportive virtual communities, while continuing to facilitate face-to-face meetings for deeper and more authentic spiritual experiences. The study concludes that future technology can be a powerful tool in developing the spirituality of STAI Al-Falah Cicalengka Bandung students who follow the Naqshbandi Tariqah, provided there is awareness of its risks and limitations.